The Relationship between Sleep Quality and Physical Fitness in Futsal Athletes - Bangbang Syamsudar; Akhmad Sobarna; Ahmad Afandi Harja (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study aims to determine the influence of sleep quality on cardiorespiratory physical Fitness in Futsal Student Activity Unit STKIP Pasundan Cimahi athletes. This research is a Correlational Descriptive research using survey and experimental methods with data collection techniques using the PSQI questionnaire to measure sleep quality and the Bleep Test to measure cardiorespiration in STKIP Pasundan Cimahi Futsal Student Activity Unit athletes. In this study, 20 athletes were sampled using the sampling method, namely total sampling. Based on the problems studied and the type of correlational descriptive research, data is used to correlate sleep quality and bleep test results to measure cardiorespiration. The results of maintaining good sleep quality on the physical fitness of Futsal Student Activity Unit  STKIP Pasundan Cimahi athletes were obtained by calculating the correlation test that the sig. 0.380 > 0.05. These results show a significant negative relationship between sleep quality and cardiorespiratory physical fitness variables. This negative relationship means that the lower the level of sleep quality, the higher the level of cardiorespiratory physical fitness.